Removal of hexavalent chromium-contaminated water and wastewater: A review - Owlad, M.; Aroua, M.K.; Daud, W.M.A.W.; Baroutian, S. (Water Air and Soil Pollution, 2009)
Cr(VI) is a well-known highly toxic metal, considered a priority pollutant. Industrial sources of Cr(VI) include leather tanning, cooling tower blowdown, plating, electroplating, anodizing baths, rinse waters, etc. This article includes a survey of removal techniques for Cr(VI)-contaminated aqueous solutions. A particular focus is given to adsorption, membrane filtration, ion exchange, and electrochemical treatment methods. The primary objective of this article is to provide recent information about the most widely used techniques for Cr(VI) removal.